Desmoplastic fibroblastoma (collagenous fibroma) of the oral cavity - Pereira, Thais-dos Santos-Fontes (J Clin Exp Dent, 2016)
Desmoplastic fibroblastoma is benign soft tissue tumor, with fibroblastic or myofibroblastic origin, that rarely occurs in oral cavity. We reported the case of a 56-year-old man who presented a tumor in the left mandibular alveolar ridge, with slow and asymptomatic growth, with no osseous involvement. The tumor was sessile with lobulated surface, covered by healthy mucosa with erythematous areas. The lesion was excised and specimens sent to histopathology and immunohistochemistry. Histopathological exam showed a non-encapsulated fibroblastic proliferation, characterized by myofibroblasts, spindle and stellate fibroblasts with large or oval nuclei and bi or tri nucleation, immersed in an abundant hypocellular dense collagen stroma. Tumor cells were positive for vimentin, HHF35, α-smooth muscle actin and factor XIIIa. The diagnosis of desmoplastic fibroblastoma was based in the clinical history of absence of trauma related to the growth in the alveolar ridge, associated with macroscopic, microscopic and immunohistochemical features. The patient is free-diseases by eight months. Key words:Collagenous fibroma, desmoplastic fibroblastoma, neoplasm of connective and soft tissue.